Inter-Communal Relations in the Context of a Sectarian Society: Communal Fear Spawns Everyday Practices and Coping Mechanisms among the Maronites of Lebanon - Helou, Joseph P. (2022)
This paper explores why the production of communal fear via demographic and political-economic factors can explain group behavior (here the Maronites of Lebanon) in diverse ethnic, religious and sectarian plural societies rather than a strict reliance on structural and instrumental explanations. It argues that communal fear, deeply entrenched in political, socioeconomic and anthropological interpretations of groups’ fertility rates, migration patterns, land ownership and shares of industry and agriculture inter alia, can explain Maronites’ everyday practices of preferring land purchases in certain (ethno-religiously defined-) areas, occupying specific jobs and dominating certain economic sectors. While we acknowledge the role of individual cognition—Lebanese citizens’ ability—in breaking away from the clutches of group thinking, we find that many pervasive political, economic and social factors reaffirm group solidarity in plural societies; thus rendering useful the concept of communal fear in explaining how members of groups adopt everyday practices to hedge against perceived risks.